Analysis of groundwater ion abnormality and its cause of centralized drinking water sources in Jieshou City, China - Su, Guifen; Liu, Guijian; Li, Yongli; Wang, Guanyu (Frontiers in Environmental Science, 2023)
Groundwater providing drinking water to city and rural residents, which is also one of the chief water sources for commercial and agricultural activities in Jieshou City. We collected and analyzed the contents of 18 underground water source wells in Jieshou. We established whether the water met acceptable quality and characteristics above the standard. This study was conducted to determine the chemical characteristics of groundwater and abnormally high superstandard ions found in groundwater. Analyze the hydrogeological conditions of the study area through data collection; Through sample collection and sample testing, the characteristics and types of water chemistry were analyzed by means of mathematical statistics analysis and Piper chart. The genesis of water chemistry was discussed by means of Gibbs chart and correlation analysis, the proportional coefficient of ion molar concentration is used to judge the source, origin and forming process of groundwater chemical composition. The results show that the groundwater is classified as marginally alkaline water, with the composition of Na-HCO3, The cations are mainly Na+, and the anions are mainly HCO3—; According to the Ⅲ water standard of groundwater quality standard and comparing the content of each ion, Na+ and F—are the primary abnormal superstandard ions, and ions and compounds are the main occurrence states. The concentration of Na+ and F—are exceed the standard of class Ⅲ water. There was a positive correlation between the abnormal Na+ and F—, and the concentration of F— increased with the increase of monitoring depth. The causes of abnormal ions are mainly determined by the lithology of the aquifer in the study area, and most of them are fluorine-containing rocks, which are transferred into groundwater through leaching or hydration. The enrichment of Na+ and F—is influenced by the local primary geological setting, hydrochemical type, hydrogeological conditions, pH and artificial activities, and the primary geological setting is the main influencing factor.